Amyloid precursor protein-fragments-containing inclusions in cardiomyocytes with basophilic degeneration and its association with cerebral amyloid angiopathy and myocardial fibrosis. Issue 1 (December 2018) - Krämer, Lara; Brettschneider, Johannes; Lennerz, Jochen; Walcher, Daniel; Fang, Lubin; Rosenbohm, Angela; Balakrishnan, Karthikeyan; Benckendorff, Julian; Möller, Peter; Just, Steffen; Willem, Michael; Ludolph, Albert; et al.
Abstract Cardiomyopathies with intracellular inclusions are a distinct subset of cardiomyopathies whereas basophilic degeneration (BD) of the heart describes inclusions in cardiomyocytes of the aging heart, which have not yet been related to a specific disease condition or to a distinct type of protein inclusion. To address the question whether BD represents a specific pathological feature and whether it is linked to a distinct disease condition we studied 62 autopsy cases. BD inclusions exhibited an immunohistochemical staining pattern related to glycosylated, δ- or η-secretase-derived N-terminal cleavage products of the amyloid precursor protein (sAPPδ/η) or shorter fragments of sAPPη. BD aggregates were found in the myocardium of both ventricles and atria with highest amounts in the atria and lowest in the interventricular septum. The frequency of BD-lesions correlated with age, degree of myocardial fibrosis in individuals with arterial hypertension, and the severity of cerebral amyloid angiopathy (CAA). The intracytoplasmic deposition of N-terminal sAPPδ/η fragments in BD indicates a specific inclusion body pathology related to APP metabolism. The correlation with the severity of CAA, which is related to the APP-derived amyloid β-protein, supports this point of view and suggests a possible link between myocardial and cerebrovascular APP-related lesions.